Differences in metacognition between multiple sclerosis phenotypes: cognitive impairment and fatigue are key factors - Coll-Martinez, Clàudia; Salavedra-Pont, Judit; Buxó, Maria; Quintana, Ester; Quiroga-Varela, Ana; Robles-Cedeño, René; Puig, Marc; Álvarez-Bravo, Gary; Ramió-Torrentà, Lluís; Gich, Jordi (Frontiers in Psychology, 2023)
Background Cognitive impairment is present in 40–65% of patients with multiple sclerosis (pwMS). Objectively measured cognitive performance often does not match patients' subjective perception of their own performance. Objective We aimed to compare cognitive performance and subjective perception of cognitive deficits between pwMS and healthy controls (HCs), as well as the accuracy of subjective perception. Methods In total, 54 HC and 112 pwMS (relapsing–remitting, RRMS, and progressive PMS) underwent neuropsychological evaluation and completed perceived deficit, fatigue, and anxiety–depression scales. Participants were classified according to their consistency between subjective self-evaluation of cognitive abilities and objective cognitive performance to assess accuracy. Regression models were used to compare cognitive performance between groups and explore factors explaining inaccuracy in the estimation of cognitive performance. Results PMS showed greater and more widespread cognitive differences with HC than RRMS. No differences were found between pwMS and HC in the perception of deficit. PMS had higher ratios of overestimators. In explaining inaccuracy, fatigue and cognitive preservation were found to be risk factors for underestimation, whereas physical disability and cognitive impairment were risk factors for overestimation. Conclusion PwMS have metacognitive knowledge impairments. This study provides new information about metacognition, data on the prevalence of impairments over a relatively large sample of PwMS, and new insights into factors explaining it. Anosognosia, related to cognitive impairment, may be present in pwMS. Fatigue is a key factor in underestimating cognition.